Scale Development for Environmental Perception of Public Space - Ho, Robbie; Au, Wing Tung (Frontiers in Psychology, 2020)
We developed a psychometric scale for measuring the subjective environmental perception of public spaces. In the scale development process, we started with an initial pool of 85 items identified from the literature that were related to environmental perception. A total of 1,650 participants rated these items on animated images of 12 public spaces through an online survey. Using principal component analyses and confirmatory factor analyses, we identified two affective factors (comfort and activity) with 8 items and six cognitive factors (legibility, enclosure, complexity, crime potential, wildlife, and lighting) with 22 items. These eight factors represent the core attributes underlying environmental perception of public spaces. Practicality of the scale and limitations of the study are also discussed.